Quantitative evaluation of the subsequent hemorrhage with arteriography-derived hemodynamic features in patients with untreated cerebral arteriovenous malformation - Zhu, Haoyu; Liu, Lian; Chang, Yuzhou; Song, Yuqi; Liang, Shikai; Ma, Chao; Zhang, Longhui; Liang, Fei; Jiang, Chuhan; Zhang, Yupeng (Frontiers in Neurology, 2023)
Background: Patients with untreated cerebral arteriovenous malformations (AVMs) are at risk of intracerebral hemorrhage. However, treatment to prevent AVM hemorrhage carries risks. Objective: This study aimed to analyze the AVM nidus-related hemodynamic features and identify the risk factors for subsequent hemorrhage. Methods: We retrospectively identified patients with untreated AVMs who were assessed at our institution between March 2010 and March 2021. Patients with ≥6 months of treatment-free and hemorrhage-free follow-up after diagnosed by digital subtraction angiography were included in subsequent examinations. The hemodynamic features were extracted from five contrast flow-related parameter maps. The Kaplan-Meier analyses and Cox proportional hazards regression models were used to find the potential risk factors for subsequent hemorrhage. Results: Overall, 104 patients with a mean follow-up duration of 3.37 years (median, 2.42 years; range, 6-117 months) were included in study, and the annual risk of rupture was 3.7%. Previous rupture (hazard ratio [HR], 4.89; 95% confidence interval [CI], 1.16–20.72), deep AVM location (HR, 4.02; 95% CI, 1.01–15.99), higher cerebral blood volume (HR, 3.35; 95% CI, 1.15–9.74) in the nidus, and higher stasis index (HR, 1.54; 95% CI, 1.06–2.24) in the nidus were associated with subsequent hemorrhage in untreated AVMs. Conclusions: Higher cerebral blood volume and stasis index in the nidus suggest increased blood inflow and stagnant blood drainage. The combination of these factors may cause subsequent hemorrhage of AVMs.